Impact of long-term climate change on Moluccella bucharica (B. Fedtsch.) Ryding population decline in Uzbekistan - Khabibullaev, Bekhruz Sh; Shomurodov, Khabibullo F; Adilov, Bekhzod A (Plant Science Today, 2022)
The article provides a comprehensive analysis of long-term climate change trends in the distribution of the endemic population of Moluccella bucharica (B. Fedtsch.) Ryding in southern Uzbekistan. Based on the analysis of daily data of 2 meteorological sources (NASA POWER and Boysun (M-II), reliable long-term trends in changes in the amounts of atmospheric precipitation and air temperatures (average, average minimum, absolute minimum, average maximum and absolute maximum) for different periods (1982–2020) of the year (year, half-year, season) have been established, which are actively manifested in the dynamics of the M. bucharica population. The results of this study serve to substantiate and explain that the conditions that lead to the M. bucharica crisis - changes in the reproductive phase and damage to seeds by insects - are the result of the effects of climate change. We found that the amplitude of the change of sediments is 59.8%, the amplitude of the change of the average temperature of the air is 19.3–53.76%, the amplitude of the change of the average maximum temperature of the air is 9.75–47.54%, the average minimum temperature of the air is 29–59%. These coefficients of change indicate that the climate of the region where the species grows has changed and is changing towards a sharp aridization.